FORMULATION DEVELOPMENT AND CHARACTERIZATION OF TEA TREE OIL LOADED ETHOSOMES - Vijayan Venugopal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
To prepare ethosomes containing tea tree oil by hot homogenization method and to evaluate its physical characters and in-vitro release pattern. the preformulation studies were carried out by standard procedure. The morphology of globule was studied by optical microscopy. The globule size and zeta potential was determined by Zetasizer, respectively and in-vitro study was done by diffusion method and the drug content was analyzed by HPTLC method. The release kinetics was also studied by fitting into few mathematical models. All the formulations were showed spherical and unilamellar shape with globule size of 931 to 975 nm, the zeta potential in the range of – 40 to -52 mV and entrapment efficiency was 57 to 65 %. Finally the invitro release studies showed the drug release from the ethosomal vesicles was burst release at initial time followed by sustained release over throughout the study. From the above consideration of evaluation studies, the tea tree oil loaded ethosomal formulation F5 shows best globule size, zeta potential and entrapment efficiency. The sustained action was confirmed by invitro release studies. All the formulations are followed zero order drug release and diffusion type of mechanism of drug releases with Fickian model. Ethosome loaded tea tree oil could be the best choice for topical application.